Comparison of reproductive performance of Clarias batrachus (Linnaeus, 1758) collected from three Indian rivers - Charan, Ravi; Dube, Kiran; Babu, P. P. Suresh; Roy, S. Dam; Sharma, Rupam; Rao, P. Srinivasa; Prasad, J. Krishna; Angel, J. Raymond Jani (Indian Journal of Fisheries, 2016)
A study was conducted to compare the reproductive performance of Clarias batrachus (Linnaeus, 1758) collected from three different rivers viz., Krishna in Andhra Pradesh, Godavari in Maharashtra and Narmada in Madhya Pradesh. Twenty pairs of brooders from each location were randomly selected and induced with pituitary extract (P) and ovaprim (O). Reproductive performance in terms of stripping percentage, pseudo gonado-somatic index, spawning, fecundity, fertilisation rate, hatching rate and survival rate as well as fry rearing performance in terms of percentage weight gain, specific growth rate (SGR) and survival rate were monitored. Brooders collected from Godavari exhibited significantly (p<0.05) higher values for all the reproductive performances indicators compared to brooders collected from Narmada and Krishna rivers. But fishes collected from Krishna River exhibited significantly higher (p<0.05) fry survival. Fry produced from Godavari brooders attained highest (p<0.05) percentage weight gain (1085.88±37.41), SGR (17.61±0.19) and fry survival rate (43.67±1.45) in comparison to Narmada. Results clearly indicated that reproductive performance varied significantly among the brooders collected from the three different rivers.